Les virus marins Simples parasites ou acteurs majeurs des écosystèmes aquatiques ? - Jacquet, Stéphan (éditions Quae, 2023)
Viruses continue to fascinate and frighten us because of their pathogenic nature for plants and animals. In the seas and oceans, they are major players in the functioning of ecosystems. Viruses are the smallest, most abundant and most diverse biological entity known to date in the marine environment, where they perform multiple functions. In addition to their role in cell death and the redistribution of matter, viruses are also a powerful vector for the evolution of their hosts and represent a major source of genetic diversity, rich in discoveries for fundamental and applied research. This book aims to shed light on an invisible biological community that is essential to understanding and explaining the functioning of the oceans. The authors, specialists in the ecology and evolution of aquatic viruses, show how viruses regulate the microbial ecosystems at the base of the ocean's food chains and how their action could, if necessary, affect the climate. This book is intended for students of life and earth sciences, teachers, researchers and academics, as well as for the general public interested in the subject of viruses and oceans.